Determinants of Inflation In Libyan Economy. - الحوتة, د. أحمد علي (Dirasat in Economics and Business, 2021)
The main purpose of this papar is to investigate the short and the long run determinants of inflation in Libyan economy for the period (1980 - 2010) by using a Autoregressive Distributed Lags Model (ARDL) technique. The consumer price index (CPI) has been utilized as an independent variable, and The gross domestic product (GDP), the budget deficit (BD), The Exchange Rate (EXC), the oil price (OP), and the foreign prices (FP), as dependent variables. The empirical results confirm the existence of co-integration relationship among the above variables. All these variables have significant effects on the inflation in the